Respuesta :

9514 1404 393

Answer:

  y = 2x -6

Step-by-step explanation:

One form you can use for this purpose is ...

  (x2 -x1)(y -y1) = (y2 -y1)(x -x1)

Filling in the given point values, this is ...

  (0 -4)(y -2) = (-6 -2)(x -4)

  -4y +8 = -8x +32

Generally, we like the equation to have coefficients with no common factors. All of these coefficients can be divided by -4.

  y -2 = 2x -8

This can be rearranged to any form you may like--or left as is.

  y = 2x -6 . . . . . slope-intercept form